2018
DOI: 10.1620/tjem.244.53
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Y-Box-Binding Protein-1 in Hind-Limb Muscles During Regeneration from Ischemic Injury in Mice

Abstract: Critical limb ischemia (CLI) is the most severe complication of peripheral arterial disease (PAD). Understanding the molecular mechanisms underlying tissue repair after CLI is necessary for preventing PAD progression. Y-box binding protein-1 (YB-1) regulates the expression of many genes in response to environmental stresses. We aimed to determine whether YB-1 is involved in ischemic muscle regeneration. A mouse ischemic hind-limb model was generated; namely, the femoral, saphenous, and popliteal arteries in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…However, on day 14, a decrease in MyoD1 level was observed in regenerated muscles treated with the PGE 2 matrix (Additional file 1 : Fig. S3A–C), which coincides with previous findings [ 40 ], implying that the PGE 2 matrix accelerated the time course of MyoD1 and further promoted the completion of muscle regeneration. Furthermore, the proliferation-associated factor, Ki-67, at the protein level, as evidenced by immunofluorescence analyzes, points to increased cellular proliferation in the response of the PGE 2 matrix to ischemic limbs (Fig.…”
Section: Resultssupporting
confidence: 91%
“…However, on day 14, a decrease in MyoD1 level was observed in regenerated muscles treated with the PGE 2 matrix (Additional file 1 : Fig. S3A–C), which coincides with previous findings [ 40 ], implying that the PGE 2 matrix accelerated the time course of MyoD1 and further promoted the completion of muscle regeneration. Furthermore, the proliferation-associated factor, Ki-67, at the protein level, as evidenced by immunofluorescence analyzes, points to increased cellular proliferation in the response of the PGE 2 matrix to ischemic limbs (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In addition, YB1 is primarily localized in the cytoplasm but can be translocated to the nucleus in response to various environmental stresses (Kohno, Izumi, Uchiumi, Ashizuka, & Kuwano, 2003), and this study revealed that YB1 nuclear transfer occurred simultaneously with upregulation of the YB1 expression. Given these results and those of previous studies on the roles of YB1 in I/R (Dong et al, 2015; Fuke et al, 2018; Hanssen et al, 2013), we conclude that YB1 may play a role in myocardial infarction injury and that this role may be related to the SHP‐1‐dependent STAT3 pathway.…”
Section: Discussionsupporting
confidence: 84%
“…The roles of YB1 in various types of I/R injury have been studied. For example, Fuke et al (2018) noted that during muscle regeneration after ischemic injury, the YB1 expression increased and was associated with myogenic differentiation antigen and alpha‐smooth muscle actin expression and improved muscle function (Fuke et al, 2018). In renal I/R injury, YB1 is required for the nephro‐ and cytoprotective effects of activated protein C in vivo and in vitro (Dong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The RNA pulldown, radioimmune precipitation, and fluorescense in situ hybridization assays confirmed that circNfix interacts with Ybx1. As an important transcription factor associated with cell proliferation, Ybx1 is involved in embryogenesis, 35 muscle regeneration, 36 oncogenic cell transformation, 37 and cardiomyocyte differentiation/dedifferentiation. 38,39 In the current study, Ybx1 induced cardiomyocyte proliferation by increasing cyclin A and cyclin B1 transcription, suggesting Ybx1 as an essential regulator of cardiac regeneration.…”
Section: Discussionmentioning
confidence: 99%